Patent Power. - Goldstein, H.
This paper presents the results of IEEE Spectrum's first annual patent survey involving 1,027 organizations with the most influential patent portfolios. The survey found that Micron Technology's patent portfolio beat out not only IBM's but also those of such perennial patent powerhouses as Hewlett-Packard, Intel, and Microsoft. The survey also rated patent companies in such categories as aerospace and defense, computer peripherals and storage, computer systems and software, electronics, medical equipment and instruments, semiconductor equipment manufacturing, semiconductor manufacturing, telecom equipment, and telecom services
Keywords: IEEE Spectrum first annual patent survey; Micron technologies; Memory chips; Patent portfolios